Aluminum battery and preparation method and application thereof

By using sulfur-graphite-carbon felt composite electrodes and specific electrolytes to treat aluminum batteries, the problems of low discharge voltage and high corrosion rate of traditional aluminum batteries are solved, and efficient energy storage performance is achieved.

CN120545485APending Publication Date: 2025-08-26SHENZHEN HAINENG CHANGCHUAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510683202.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Traditional aluminum batteries have high impedance of Al2O3 passivation layer on the surface, resulting in low discharge voltage, severe polarization, fast circulation capacity attenuation, severe hydrogen evolution of magnesium-aluminum alloy negative electrode, high corrosion rate, short battery life, and low energy storage efficiency.

Method used

The sulfur-graphite-carbon felt composite electrode is used as the positive electrode, and the aluminum negative electrode is treated with a specific proportion of electrolyte and corrosion inhibitor. The sulfur and graphite are mixed by ball milling or ultrasonic waves, and loaded on the carbon felt, heat treatment and cooling molding are carried out to form an aluminum battery.

Benefits of technology

It improves the circulation capacity of aluminum batteries and reduces the corrosion rate, extends the battery life, and meets the requirements of efficient energy storage equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120545485A_ABST
    Figure CN120545485A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum battery as well as a preparation method and application thereof, belongs to the technical field of electrochemical energy storage, and solves the problems of fast cycle capacity fading and high corrosion rate of an existing battery. The preparation method of the aluminum battery comprises the following steps: S1, putting aluminum into an electrolyte to obtain a negative electrode; and S2, adopting a sulfur-graphite-carbon felt composite electrode as a positive electrode, and forming the battery by the electrolyte, the negative electrode and the positive electrode. The aluminum battery prepared by the preparation method disclosed by the invention is good in performance, high in cycle capacity and low in corrosion rate; the aluminum battery prepared by the method can be applied to efficient energy storage equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to an aluminum battery and a preparation method and application thereof. Background Art

[0002] Batteries are currently widely used in daily life, but capacity decay is inevitable during use. Traditional aluminum batteries have a high impedance Al2O3 passivation layer on the surface, resulting in low discharge voltage (<1.6V), severe polarization, and rapid cycle capacity decay. Traditional magnesium-aluminum alloy negative electrodes have severe hydrogen evolution and high corrosion rates, which shortens the battery life and reduces the battery energy storage efficiency, making the battery unsuitable for use in energy storage devices. Summary of the Invention

[0003] The purpose of the present invention is to provide an aluminum battery and its preparation method and application, which solve the problems of rapid cycle capacity decay and high corrosion rate of existing batteries.

[0004] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] A method for preparing an aluminum battery comprises the following steps:

[0006] Step S1, placing aluminum into an electrolyte to obtain a negative electrode;

[0007] Step S2: using a sulfur-graphite-carbon felt composite electrode as a positive electrode, and the electrolyte, the negative electrode and the positive electrode form a battery.

[0008] In some embodiments, the electrolyte includes a solvent, an active agent, and a thickener, wherein the active agent and the thickener are dissolved in the solvent, and the molar volume ratio of the active agent to the thickener is (1-10): (0.5-2).

[0009] In some embodiments, the electrolyte further includes a corrosion inhibitor, and the mass ratio of the corrosion inhibitor to the solvent is 0.1-1.5:1.

[0010] In some embodiments, the solvent is any one of a water / ethylene glycol mixture, a water / diethylene glycol mixture, a water / triethylene glycol mixture, a water / propylene glycol mixture, a water / butylene glycol mixture or a water / propylene alcohol mixture, the active agent is potassium iodide and iodophor, the thickener is polyacrylamide or alkanolamide, and the corrosion inhibitor is thiourea.

[0011] In some embodiments, in step S2, the preparation method of the sulfur-graphite-carbon felt composite electrode is:

[0012] Step S21, mixing sulfur and graphite, and loading the mixed sulfur and graphite materials onto carbon felt to obtain carbon felt with sulfur and graphite loaded on the surface;

[0013] Step S22, heat-treating the carbon felt with sulfur and graphite loaded on its surface obtained in step S21 to obtain the sulfur-graphite-carbon felt composite;

[0014] Step S23: Cooling and pressing the sulfur-graphite-carbon felt composite obtained in step S22 to obtain a sulfur-graphite-carbon felt composite electrode.

[0015] In some embodiments, the mass ratio of the sulfur to the graphite in step S21 is 1:1-5, and the sulfur and the graphite are mixed by ball milling or ultrasonication.

[0016] In some embodiments, the step S21 further includes loading the sulfur and the graphite onto the carbon felt by an impregnation method.

[0017] In some embodiments, in step S22, the heat treatment temperature is 150-300° C., and the heat treatment time is 1-5 hours.

[0018] In some embodiments, in step S23, the sulfur loading in the sulfur-graphite-carbon felt composite electrode is 5-10 mg / cm 2 .

[0019] Another technical solution of the present invention is achieved as follows: an aluminum battery is prepared using the aluminum battery preparation method.

[0020] Another technical solution of the present invention is achieved as follows: aluminum batteries are used in energy storage devices.

[0021] Compared with the prior art, the aluminum battery prepared by the preparation method of the present invention has good performance, high cycle capacity and low corrosion rate; the aluminum battery prepared by the present invention can be applied to high-efficiency energy storage equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A flow chart of a method for preparing an aluminum battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0024] In the description of the present invention, it should be clarified that the terms "vertical", "transverse", "longitudinal", "front", "rear", "left", "right", "up", "down", "horizontal", etc. indicating orientation or positional relationship are based on the orientation or positional relationship shown in the accompanying drawings, which is only for the convenience of describing the present invention, and does not mean that the device or element referred to must have a specific orientation or position, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, it should be noted that, unless otherwise clearly stipulated and limited, the terms "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. A method for preparing an aluminum battery provided in an embodiment of the present invention includes the following steps:

[0025] Step S1, placing aluminum into an electrolyte to obtain a negative electrode;

[0026] Step S2: using a sulfur-graphite-carbon felt composite electrode as a positive electrode, and the electrolyte, the negative electrode and the positive electrode form a battery.

[0027] In a specific implementation process, the electrolyte includes a solvent, an active agent, and a thickener, the active agent and the thickener are dissolved in the solvent, and the molar volume ratio of the active agent to the thickener is (1-10): (0.5-2); the electrolyte also includes a corrosion inhibitor, and the mass ratio of the corrosion inhibitor to the solvent is 0.1-1.5:1; the solvent is any one of a water / ethylene glycol mixture, a water / diethylene glycol mixture, a water / triethylene glycol mixture, a water / propylene glycol mixture, a water / butylene glycol mixture or a water / propylene alcohol mixture, the active agent is potassium iodide and iodophor, the thickener is polyacrylamide or alkanolamide, and the corrosion inhibitor is thiourea.

[0028] In a specific implementation process, in step S2, the preparation method of the sulfur-graphite-carbon felt composite electrode is:

[0029] Step S21: mixing sulfur with graphite, and loading the mixed sulfur and graphite materials onto carbon felt to obtain a carbon felt with sulfur and graphite loaded on the surface; the mass ratio of the sulfur to the graphite is 1:1-5, and the sulfur and the graphite are mixed by ball milling or ultrasonic treatment; in addition, the sulfur and the graphite are loaded onto the carbon felt by impregnation;

[0030] Step S22, heat-treating the carbon felt with sulfur and graphite loaded on its surface obtained in step S21 to obtain the sulfur-graphite-carbon felt composite; the heat treatment temperature is 150-300° C., and the heat treatment time is 1-5 hours;

[0031] Step S23: Cooling and pressing the sulfur-graphite-carbon felt composite obtained in step S22 to obtain a sulfur-graphite-carbon felt composite electrode; in the sulfur-graphite-carbon felt composite electrode, the sulfur loading is 5-10 mg / cm 2 .

[0032] An embodiment of the present invention also provides an aluminum battery manufactured using the above-mentioned aluminum battery manufacturing method.

[0033] The embodiments of the present invention also provide applications of the aluminum battery in energy storage devices.

[0034] The following are specific embodiments

[0035] Example 1

[0036] like Figure 1 As shown, 1.5 mol / L KI and 5 mol / L I2 were added to the water / ethylene glycol mixture and stirred thoroughly until completely dissolved. 0.5 mol / L polyacrylamide, 0.1 mol / L thiourea and 0.5 mol / L phytic acid were slowly added and stirred continuously. After uniform mixing, an electrolyte was obtained and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.05 mA / cm 2 , charge and discharge three times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 10 nm;

[0037] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:1, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before loading sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Dimethyl sulfoxide is used to dissolve the sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:1:3. 8 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 150°C for 1 hour in an inert atmosphere (such as helium, neon, argon, krypton, xenon, or radon).

[0038] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 30 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The resulting battery had a cycle life of 10,000 times, a capacity retention rate of 86%, and a hydrogen evolution rate of 0.049 mL / h.

[0039] Example 2

[0040] like Figure 1 As shown, 1.8 mol / L KI and 6 mol / L I2 were added to a water / diethylene glycol mixture and stirred thoroughly until completely dissolved. 0.8 mol / L alkanolamide, 0.2 mol / L thiourea and 0.7 mol / L phytic acid were slowly added and stirred continuously. After uniform mixing, an electrolyte was obtained and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.06 mA / cm 2 , charge and discharge 4 times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 20 nm;

[0041] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:2, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before loading sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Petroleum ether is used to dissolve sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:2:3. 7 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 180°C for 2 hours in an inert atmosphere (such as helium, neon, argon, krypton, xenon, or radon).

[0042] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 40 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The obtained battery had a cycle life of 10020 times, a capacity retention rate of 87%, and a hydrogen evolution rate of 0.048 mL / h.

[0043] Example 3

[0044] like Figure 1As shown, 1.9 mol / L KI and 7 mol / L I2 were added to a water / triethylene glycol mixture and stirred thoroughly until completely dissolved. 0.9 mol / L polyacrylamide, 0.3 mol / L thiourea, and 0.9 mol / L phytic acid were slowly added and stirred continuously. After uniform mixing, an electrolyte was obtained and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.07 mA / cm 2 , charge and discharge 4 times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 30 nm;

[0045] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:2, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before loading sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Petroleum ether is used to dissolve sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:2:3. 7 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 200°C for 3 hours in an inert atmosphere (such as helium, neon, argon, krypton, xenon, or radon).

[0046] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 40 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The resulting battery had a cycle life of 10,030 times, a capacity retention rate of 87%, and a hydrogen evolution rate of 0.048 mL / h.

[0047] Example 4

[0048] like Figure 1 As shown, 2 mol / L KI and 7 mol / L I2 were added to a water / propylene glycol mixture and stirred thoroughly until completely dissolved. 1 mol / L alkanolamide, 0.4 mol / L thiourea, and 1 mol / L phytic acid were slowly added and stirred continuously. After uniform mixing, an electrolyte was obtained and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.08 mA / cm 2 , charge and discharge 4 times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 40 nm;

[0049] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:2, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before loading sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Dimethyl sulfoxide is used to dissolve the sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:2:3. 7 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 220°C for 4 hours in an inert atmosphere (such as helium, neon, argon, krypton, xenon, or radon).

[0050] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 45 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The resulting battery had a cycle life of 10,040 times, a capacity retention rate of 88%, and a hydrogen evolution rate of 0.047 mL / h.

[0051] Example 5

[0052] like Figure 1 As shown, 2 mol / L KI and 10 mol / L I2 were added to the water / butanediol mixture and stirred thoroughly until completely dissolved. 1 mol / L polyacrylamide, 0.5 mol / L thiourea and 1.2 mol / L phytic acid were slowly added and stirred continuously. After uniform mixing, an electrolyte was obtained and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.08 mA / cm 2 , charge and discharge three times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 45 nm;

[0053] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:3, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before being loaded with sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Petroleum ether is used to dissolve sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:3:3. 8 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 250°C for 4 hours in an inert atmosphere (such as any one of helium, neon, argon, krypton, xenon, and radon).

[0054] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 50 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The obtained battery had a cycle life of 10050 times, a capacity retention rate of 87%, and a hydrogen evolution rate of 0.046 mL / h.

[0055] Example 6

[0056] like Figure 1 As shown, 2 mol / L KI and 8 mol / L I2 were added to a water / propylene alcohol mixture, stirred thoroughly until completely dissolved, and 2 mol / L alkanolamide, 0.5 mol / L thiourea, and 1.5 mol / L phytic acid were slowly added, and continued to stir. After uniform mixing, an electrolyte was obtained, and the pH of the electrolyte was controlled to be 6-7. Aluminum foil was immersed in the electrolyte for pre-circulation, and the pre-circulation current density was 0.1 mA / cm 2 , charge and discharge 4 times to prepare a negative electrode, an Al-IO passivation layer is formed on the surface of the negative electrode, and the thickness of the passivation layer is 50 nm;

[0057] Sulfur and graphite are mixed by ultrasound in a mass ratio of 1:5, and carbon felt is used as a current collector. The carbon felt is acid-washed or ultrasonically cleaned before being loaded with sulfur and graphite. The mixed sulfur and graphite materials are loaded onto the surface of the carbon felt by impregnation. Petroleum ether is used to dissolve sulfur and the treated carbon felt is immersed in it. The excess solvent is then removed by rotary evaporation or vacuum drying. The mass ratio of sulfur: graphite: carbon felt is 1:5:3. 7 mg of active sulfur is loaded per square centimeter of electrode surface. The sulfur-loaded carbon felt is heat-treated at a temperature of 300°C for 5 hours in an inert atmosphere (such as any one of helium, neon, argon, krypton, xenon, and radon).

[0058] After heat treatment, the composite electrode was naturally cooled to room temperature and formed under a pressure of 50 MPa. The sulfur-graphite-carbon felt composite electrode, positive electrode, electrolyte and separator were assembled into a battery, and preliminary charge and discharge tests were carried out to evaluate the electrochemical performance. The obtained battery had a cycle life of 10050 times, a capacity retention rate of 87%, and a hydrogen evolution rate of 0.048 mL / h.

[0059] Comparative Example

[0060] In N-methylpyrrolidone solvent, a slurry was prepared by adding carbon black:polyaniline:CMC (mass ratio = 8:1:1). This slurry was then coated onto aluminum foil, dried, rolled, and cut into electrodes of appropriate size. The cut electrodes were wound into a battery cell with a polypropylene separator and an aluminum-lithium sheet as the negative electrode material. This was then packaged into a nickel-plated steel casing. An electrolyte solution of 1-butyl-2,3-dimethylimidazolium fluoride and aluminum chloride (at a molar ratio of 1:1.4) was added, and the cell was sealed to form a cylindrical aluminum battery. The battery was charged at 1C to 2.4V and discharged to 0.5V. The initial discharge capacity was 58.5mAh / g. After 2000 cycles, the capacity retention was 80%, and the hydrogen evolution rate was 0.1mL / h.

[0061] Table 1 Parameters of batteries prepared in Examples 1-6 and Comparative Examples

[0062] Cycle life (times) Capacity retention rate Hydrogen evolution rate (mL / h) Example 1 10000 86% 0.049 Example 2 10020 87% 0.048 Example 3 10030 87% 0.048 Example 4 10040 88% 0.047 Example 5 10050 87% 0.046 Example 6 10050 87% 0.048 Comparative Example 2000 80% 0.1

[0063] In summary, as shown in Table 1, the batteries prepared in Examples 1-6 of the present invention have a high cycle life and a hydrogen evolution rate of <0.05 mL / h. The hydrogen evolution rates of Examples 1-6 pass the UL1642 certification standard. The aluminum batteries prepared by the preparation method of the present invention have good performance, high cycle capacity, and low corrosion rate; the aluminum batteries prepared by the present invention can be used in high-efficiency energy storage devices.

[0064] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.

Claims

1. A method for preparing an aluminum battery, characterized in that: The following steps are involved: Step S1, placing aluminum into an electrolyte to obtain a negative electrode; Step S2: using a sulfur-graphite-carbon felt composite electrode as a positive electrode, and the electrolyte, the negative electrode and the positive electrode form a battery.

2. The method for preparing an aluminum battery according to claim 1, wherein: The electrolyte includes a solvent, an active agent, and a thickener. The active agent and the thickener are dissolved in the solvent, and the molar volume ratio of the active agent to the thickener is (1-10): (0.5-2).

3. The method for preparing an aluminum battery according to claim 2, wherein: The electrolyte further includes a corrosion inhibitor, and the mass ratio of the corrosion inhibitor to the solvent is 0.1-1.5:

1.

4. The method for preparing an aluminum battery according to claim 3, wherein: The solvent is any one of a water / ethylene glycol mixture, a water / diethylene glycol mixture, a water / triethylene glycol mixture, a water / propylene glycol mixture, a water / butylene glycol mixture or a water / propylene alcohol mixture; the active agent is potassium iodide and iodophor; the thickener is polyacrylamide or alkanolamide; and the corrosion inhibitor is thiourea.

5. The method for preparing an aluminum battery according to claim 3, wherein: In step S2, the preparation method of the sulfur-graphite-carbon felt composite electrode is: Step S21, mixing sulfur and graphite, and loading the mixed sulfur and graphite materials onto carbon felt to obtain carbon felt with sulfur and graphite loaded on the surface; Step S22, heat-treating the carbon felt with sulfur and graphite loaded on its surface obtained in step S21 to obtain the sulfur-graphite-carbon felt composite; Step S23: Cooling and pressing the sulfur-graphite-carbon felt composite obtained in step S22 to obtain a sulfur-graphite-carbon felt composite electrode.

6. The method for preparing an aluminum battery according to claim 5, wherein: In the step S21 , the mass ratio of the sulfur to the graphite is 1:1-5, and the sulfur and the graphite are mixed by ball milling or ultrasonic treatment.

7. The method for preparing an aluminum battery according to claim 5, wherein: The step S21 further includes loading the sulfur and the graphite onto the carbon felt by an impregnation method.

8. The method for preparing an aluminum battery according to claim 5, wherein: In the step S22, the temperature of the heat treatment is 150-300°C, and the time of the heat treatment is 1-5 hours.

9. The method for preparing an aluminum battery according to claim 8, wherein: In step S23, the sulfur loading in the sulfur-graphite-carbon felt composite electrode is 5-10 mg / cm 2 .

10. An aluminum battery, characterized in that: The aluminum battery is prepared by the preparation method of any one of claims 1 to 9.

11. Use of the aluminum battery according to claim 10 in energy storage equipment.